Optimizing the Cas13 antiviral train: cargo and delivery - Shruti Sharma; Cameron Myhrvold (EMBO Molecular Medicine)
Abstract The severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic in 2020 highlighted the need for rapid, widespread responses against infectious disease. One such innovation uses CRISPR‐Cas13 technology to directly target and cleave viral RNA, thereby inhibiting replication. Due to their programmability, Cas13‐based antiviral therapies can be rapidly deployed to target emerging viruses, in comparison with traditional therapeutic development that takes at least 12–18 months, and often many years. Moreover, similar to the programmability of mRNA vaccines, Cas13 antivirals can be developed to target mutations as the virus evolves.